Managing water resources for sustainable socioeconomic development a country water assessment for the People Republic of China. (Asian Development Bank, 2018)
This study provides an overview of the water security situation in the People Republic of China.It assesses the policy and institutional requirements for addressing issues and recommends strategic areas for strengthening and reform. The five dimensions of water security covered in the research are domestic water security, economic production water security, environmental water security, ecological water security, and resilience to water related disasters. A summary of key policy recommendations identifies the essential measures needed to effectively move forward the alleviation of water security issues in different time frames.